Role of Bacteroides bivius beta-lactamase in beta-lactam susceptibility. - Lacroix, J M (1984)
The susceptibility of 46 clinical isolates of Bacteroides bivius to amoxicillin, cefotaxime, cefoxitin, ceftizoxime, cephaloridine, cephalothin, moxalactam, penicillin G, amoxicillin plus clavulanic acid in a ratio of 2:1, carbenicillin, cefamandole, and ceftazidime was determined by an agar dilution technique. For the first eight agents susceptibility testing was also done with the addition of clavulanic acid (0.75 microgram/ml). For all agents, beta-lactamase-positive strains (35, using a nitrocefin slide test) were inhibited at higher concentrations than beta-lactamase-negative strains. Clavulanic acid reduced the susceptibility of the beta-lactamase-positive strains to the level of the beta-lactamase-negative strains to all agents. We prepared crude extracts of beta-lactamase from six strains. Activity against nitrocefin was directly related to their susceptibilities. The beta-lactamase had a mixed-substrate profile, hydrolyzing both penicillins and cephalosporins. Our results suggest a slow inactivation of cefoxitin, ceftizoxime, and moxalactam by the beta-lactamase. Clavulanic acid and cefoxitin inhibited the enzyme, whereas p-hydroxymercuribenzoate and cloxacillin did not. Thus, there was a clear relationship between beta-lactamase activity and susceptibility to beta-lactams, including cefoxitin and third-generation cephalosporins. The substrate and inhibition profiles of the B. bivius beta-lactamase were different from those of enzymes found in the "B. fragilis group."